Pengaruh Keterampilan Sosial terhadap Komitmen Organisasi Pengurus UKK-KOPMA UIN Antasari Banjarmasin - Amin, Muhammad Hasan; Suriadi, Ahmad; Komalasari, Shanty (Jurnal Al-Husna, 2020)
Organization is a group formed in order to achieve specified goals. This goal can be achieved if the management in it has a good organizational commitment. There are several factors that influence a person in increasing his organizational commitment. One of them is a factor in him, namely in the form of social skills. So the existence of this study aims to determine the effect of social skills on organizational commitment UKK-KOPMA UIN Antasari Banjarmasin. The hypothesis proposed in this study is that there is a significant positive effect between social skills and organizational commitment. This research is quantitative with purposive sample sampling technique. The research data collection instrument used a Likert scale model and data analysis used simple linear regression analysis with the help of SPSS. The results of this study indicate that the significant value of the influence of social skills on organizational commitment is 0.048 lower than the significant standard, namely 0.05 (0.048 <0.05), which means that there is an influence between social skills and organizational commitment of the UKK-KOPMA management at UIN Antasari Banjarmasin for the period 2018/2019. . Then, the R square value is 0.096, which means that the social skills variable has an influence on organizational commitment by 9.6% and the rest is influenced by other factors.